Migration, fidelity, and use of autumn staging grounds in Alaska by Cackling Canada Geese Branta canadensis minima - Gill, Robert E; Babcock, Christopher A; Handel, Colleen M; Butler, Jr, William R; Raveling, Dennis G (Wildfowl, 1996)
Cackling Canada Geese were studied annually (1985-88) on autumn migration staging areas in Alaska during a period of rapid population growth. Geese concentrated at two estuaries (Ugashik Bay and Cinder Lagoon) along the north side of the Alaska Peninsula. Birds arrived on the staging areas in late September, numbers peaked during mid-October, and departure occurred by late October or early November. Annual peak counts combined for the two staging areas ranged from 16,000-54,000 geese, or from 23-120% of the autumn population index. Up to 30,000 geese were recorded at each estuary, but relative use of the two staging areas varied among years. Within-year fidelity to staging areas was high; only three of 242 neck-banded geese seen more than once were observed at both areas within a season. Between-year fidelity to staging areas was highest among hatching-year females (11 of 11) and adult males (14 of 17), lowest among hatching-year males (4 of 9), and intermediate among adult females (18 of 28). Use of the two staging areas was independent of family status, reproductive status, and age. Late arrivals on the staging areas consisted of a higher proportion of single and paired birds than of geese in family groups. Most geese departed the staging grounds with the onset of freezing conditions and the passage of low pressure systems that produced winds favourable for migration. Transoceanic flights to the wintering grounds in Oregon and California were completed in about 48 h. During years with mild weather on the breeding grounds and years with early freezing conditions on the staging areas, few geese staged on the Alaska Peninsula, indicating that geese can sometimes obtain sufficient energy reserves to migrate directly from the breeding grounds without stopping on the staging areas. Only 25% of the area used for staging is legally protected. Use of unprotected areas may become increasingly important if the population continues to increase.